Investigating physical parameters potentially associated with mass coral bleaching events in the Coral Triangle - Peñaflor, Eileen L.; David, Laura T. (Quezon City Marine Science Institue, College of Science, University of the Philippines Diliman, 2016)
The rising temperature of the ocean, together with the frequent occurence of thermal anomalies, has become one f the major concerns.Intense anomalies in sea temperatures have resulted in coral bleaching occurrences, and even led to coral mortality in various parts of the world. This study investigates the patterns in the timing and extent of anomalies of some parameters associated with coral bleaching occurrences in the Coral Triangle. These parameters include sea surface temperature (SST), wind speed, cloudiness, and photosynthetically active radiation 9PAR). Investigation of the Interyropical Convergence Zone (ITCZ) latitude position is also included since this parameteris said to be affected y El Niño Southern Oscillation (ENSO) and might provide additional insight to the process that favors coral bleaching occurrence.
Dissertation (Ph.D. Marine Science)--University of the Philippines Diliman
Keywords: Coral bleaching and climate change; Coral bleaching and thermal stress